Análise fotoelástica da distribuição de tensões peri-implantares em overdenture mandibular retida por implante unitário com diferentes tipos de conexão - Nascimento, João Francisco Machado do (2013)
For patients poorly adapted to conventional dentures, the single-implant mandibular overdenture has been proposed as a simplified alternative for the two-implant treatment, together with the use of immediate loading of the implant. The aim of this in vitro study was to compare the photoelastic characteristics of stress transfer to the implant in a single-implant mandibular overdenture using different types of attachments. A photoelastic model of an edentulous mandible with a resilient edentulous ridge and a unique implant located at the symphyseal region was obtained to reproduce a single implant-retained mandibular overdenture. Six 2.0 mm height attachments were selected and inserted in the same photoelastic model in a random order. A universal material testing machine was used to induce axial vertical loads of 70 N applied in the central incisor and in the central region of the first right molar without contact on the contralateral side. The photoelastic analysis was performed using a polariscope integrated into the testing machine. Standard separate views were photographed and evaluated visually for stress-induced fringes, to comparatively rank the different attachment systems. All attachments showed a similar tension distribution concentrated in the apical third, and the highest stress concentration at the apical level. There was a low stress concentration at the coronal third of the implant, with no discernible stress in the first threads of the implants, except for Dalla Bona which showed low stress at the coronal part of the implant (one fringe). No identifiable fringes were observed when the load was applied in the molar region, which resulted from the low amount of stress transmitted by the implant for all attachments. It was concluded that the load transferred to a single mandibular implant is low and within the limits of functional loading, irrespective of the type of retention system.